INDIGENOUS GENOCIDE TODAY: KAIOWCIDE AND THE GUARANI-KAIOWA ETHNOPOLITICAL TRAGEDY - A. R. Ioris, Antônio (REVISTA ESMAT, 2023)
The indigenous genocide unfolding in the Brazilian State of Mato Grosso do Sul – described here as Kaiowcide – is not just a case of hyperbolic violence, but it is something qualitatively different from other serious crimes committed against marginalised, subaltern communities in the rest of the country. Kaiowcide is the reincarnation of old genocidal practices of agrarian capitalism that once again target the Guarani-Kaiowa indigenous people because of their land-based ethnopolitical demands. The present analysis is based on a novel interpretation of indigenous genocides through the nexus between genocide-geocide-massacre. Considering that politico-spatial nexus, Kaiowcide combines strategies and procedures based on the competition and opposition between groups of people who dispute the relatively scarce social opportunities of an agribusiness-based economy that characterises the region.